Does perception equal reality? Weight misperception in relation to weight-related attitudes and behaviors among overweight and obese US adults - Ding Eric L; Scharoun-Lee Melissa; Wolin Kathleen Y; Duncan Dustin T; Warner Erica T; Bennett Gary G (BMC, 2011)
Abstract Background Weight misperception might preclude the adoption of healthful weight-related attitudes and behaviors among overweight and obese individuals, yet limited research exists in this area. We examined associations between weight misperception and several weight-related attitudes and behaviors among a nationally representative sample of overweight and obese US adults. Methods Data from the 2003-2006 National Health and Nutrition Examination Survey (NHANES) were used. Analyses included non-pregnant, overweight and obese (measured body mass index ≥ 25) adults aged 20 and older. Weight misperception was identified among those who reported themselves as "underweight" or "about the right weight". Outcome variables and sample sizes were: weight-loss attitudes/behaviors (wanting to weigh less and having tried to lose weight; n = 4,784); dietary intake (total energy intake; n = 4,894); and physical activity (meets 2008 US physical activity recommendations, insufficiently active, and sedentary; n = 5,401). Multivariable regression models were stratified by gender and race/ethnicity. Analyses were conducted in 2009-2010. Results These overweight/obese men and women who misperceived their weight were 71% (RR 0.29, 95% CI 0.25-0.34) and 65% (RR 0.35, 95% CI 0.29-0.42) less likely to report that they want to lose weight and 60% (RR 0.40, 95% CI 0.30-0.52) and 56% (RR 0.44, 95% CI 0.32-0.59) less likely to have tried to lose weight within the past year, respectively, compared to those who accurately perceived themselves as overweight. Blacks were particularly less likely to have tried to lose weight. Weight misperception was not a significant predictor of total energy intake among most subgroups, but was associated with lower total energy intake among Hispanic women (change -252.72, 95% CI -433.25, -72.18). Men who misperceived their weight were less likely (RR 0.68, 95% CI 0.52-0.89) to be insufficiently active (the strongest results were among Black men) and women who misperceived their weight were less likely (RR 0.74, 95% CI 0.54, 1.00, p = 0.047) to meet activity recommendations compared to being sedentary. Conclusion Overall, weight misperception among overweight and obese adults was associated with less likelihood of interest in or attempts at weight loss and less physical activity. These associations varied by gender and race/ethnicity. This study highlights the importance of focusing on inaccurate weight perceptions in targeted weight loss efforts.